2020
DOI: 10.5498/wjp.v10.i11.272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smartphone-based interventions and monitoring on bipolar disorder: A systematic review and meta-analysis

Abstract: BACKGROUND Recently, there has been a range of studies about smartphone-based interventions and monitoring for reducing symptoms of bipolar disorder (BD). However, their efficacy for BD remains unclear. AIM To compare the effect of smartphone-based interventions and monitoring with control methods in treating patients with BD. METHODS A systematic literature search was performed on PubMed, Embase, Clinical trials, psycINFO, Web of Science, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…A recent meta‐analysis compared the effect of smartphone‐based interventions and monitoring with control methods in BD 60 . This study concluded that smartphone‐based interventions in BD are effective in reducing manic and depressive symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis compared the effect of smartphone‐based interventions and monitoring with control methods in BD 60 . This study concluded that smartphone‐based interventions in BD are effective in reducing manic and depressive symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis concerning the efficacy of digital interventions in bipolar disorder found positive effects on both depressive and manic symptoms 118 , but only four of the ten included studies were randomized controlled trials 45,119‐121 . As to unipolar depressive disorder, while an increasing number of randomized controlled trials of apps with psychotherapy‐related content have been published 26 , several of them have shown no evidence that delivering psychological interventions via smartphone confers a significant advantage beyond control conditions 122‐124 .…”
Section: Evidence For Digital Psychiatry Within Specific Contextsmentioning
confidence: 99%
“…Eine technologische Analyse könnte für die zwischenmenschliche Beziehung von Vorteil sein. Es könnte sein, dass m-health Produkte als Zusatz- oder Einzeltherapie einen Vorteil gegenüber der derzeitigen Therapie bringen können 37 , auch wenn derzeit aufgrund der Heterogenität der Produkte und fehlenden Goldstandards keine generellen Empfehlungen für das Monitoring bipolarer PatientInnen ausgesprochen werden kann 38 . In der Vergangenheit waren ÄrztInnen und TherapeutInnen auf subjektive, retrospektive Informationen angewiesen.…”
Section: Diskussionunclassified